Berwirausaha Ikan Lele Menjadi Produk Bernilai Guna Peningkatan Pendapatan Petani - Westim Ratang; Elimelek Ramandey (Jurusan Manajemen dan Bisnis Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2022)
This activity aims to develop catfish entrepreneurship into a valuable product, increase the income of farmers in Koya Koso Abepura, and improve their skills in processing catfish into products that are ready to sell and provide management knowledge to farmers in Koya Koso Abepura. The implementation of Community Service Activities are carried out offline or face-to-face and questionnaires. The impact of training on making catfish floss on farmers who initially did not know finally knew and wanted to try entrepreneurship to increase family income and business of farmers in Koya Koso.